SEPAK TERJANG SARWO EDHIE WIBOWO DALAM MENJAGA STABILITAS KEAMANAN NASIONAL INDONESIA (1965-1989) - Nurodin, Acep; Saripudin, Didin; Kamsori, Moch Eryk (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
This research entitled â€œThe Action of Sarwo Edhie Wibowo in Maintaining Stability of Indonesia National Security (1965-1989)â€. The Main problem in this research is â€œHow was Sarwo Edhie Wibowoâ€™s Action in Maintaining Indonesian National Security (1965-1989)â€. The Research methodology used in this research is historical method through many steps such as heuristic, source criticism, interpretation and historiography. The researcher used interdisciplinary approaches through sociology and politic study. Sarwo Edhie Wibowoâ€™s position as Commander of The Command of The Army Regiment (RPKAD) was most attracted era. Based on the command of PANGKOSTRAD Major General Soeharto, Sarwo Edhie succeeded to overcome coup of 30th September Movement. Entering New Order era, Sarwo Edhie officiated as Pangdam II/Bukit Barisan and helped in PNI stopping operation in North Andalas and then became Pangdam XVII/Cendrawasih. As Pangdam XVII/Cendrawasih, Sarwo Edhie had a role in succeeding PEPERA execution. In the end of his career, Sarwo Edhie became Governor of AKABRI, ambassador in South Korea, Head of BP7, and last as member of DPR/MPR. Until the end, he was retired and passed away at 10th November 1989.